(3QSGdI aj HjGf GdML GdeHQhQs - (3GdHNGQj, CejQ HGOTGg, eMeO Cejf Hf eMehO, (B987(3g`s
(3BNQgG (B:s
(3aj BNQgG fbd ef cJGH JgfjFI GdGSdGe HJLOjO HjJ GdMQGe, dGHQGgje GdeGehfj, hcPdc bd ef MGTjI Ydi JaSjQ ShQI GdfHC ddHjVGhjs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdeYGQa GdYGeIs